2021
DOI: 10.3390/biomedicines9070846
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Depletion Promotes Human Rotavirus Replication in an Adult Mouse Model

Abstract: Intestinal microbiota-virus-host interaction has emerged as a key factor in mediating enteric virus pathogenicity. With the aim of analyzing whether human gut bacteria improve the inefficient replication of human rotavirus in mice, we performed fecal microbiota transplant (FMT) with healthy infants as donors in antibiotic-treated mice. We showed that a simple antibiotic treatment, irrespective of FMT, resulted in viral shedding for 6 days after challenge with the human rotavirus G1P[8] genotype Wa strain (RVwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 53 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Thus, bacteria belonging to lactobacilli, Mucispirillum, Oscillospira, and Bilophila genera were negatively linked to RV infection in mice. Faecal material transplantation with infants as donors did not restrict infectivity in this model, suggesting that the microbiota from the donors was not able to control RV infection in this model and that mice autochthonous bacteria were needed for the process [96]. Although differences depending on the host and viral strains cannot be excluded, all these data point to the microbiota as a major factor limiting RV replication.…”
Section: Microbiota and Restriction Of Enteric Viral Infectionsmentioning
confidence: 79%
See 3 more Smart Citations
“…Thus, bacteria belonging to lactobacilli, Mucispirillum, Oscillospira, and Bilophila genera were negatively linked to RV infection in mice. Faecal material transplantation with infants as donors did not restrict infectivity in this model, suggesting that the microbiota from the donors was not able to control RV infection in this model and that mice autochthonous bacteria were needed for the process [96]. Although differences depending on the host and viral strains cannot be excluded, all these data point to the microbiota as a major factor limiting RV replication.…”
Section: Microbiota and Restriction Of Enteric Viral Infectionsmentioning
confidence: 79%
“…Recently, it has been shown that microbiota ablation with antibiotics in mice allows for infection with the human RV strain Wa (G1P [8]), which replicates very inefficiently in animals with normal microbiota [96]. These results are in conflict with earlier experiments which demonstrated that microbiota eradication by antibiotics results in reduced infection of murine RV (EC strain), as shown by lower viral shedding in adult mice and diminished diarrhea incidence in mice pups [84].…”
Section: Microbiota and Restriction Of Enteric Viral Infectionsmentioning
confidence: 90%
See 2 more Smart Citations
“…Mechanistically, the interaction between gut microbiota and viruses seems to stabilize enteric viruses, enhance their adhesion to host cells, inhibit antibody production, and create a conducive environment for viral replication and immune evasion [125]. Conversely, several studies found that antibiotic-treated or germ-free animal models have higher rotavirus replication and more severe symptoms, which can be mitigated by FMT [124,126,127]. An elevated abundance of Akkermansia and a reduced abundance of Faecalibacterium were correlated with higher levels of viral antibodies [128].…”
Section: Interaction Of Gut Microbiome and Enteric Virusesmentioning
confidence: 99%